(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Background. Soil microbiological activity plays a fundamental role in sustaining agroecosystem functionality, environmental safety, and human health. In intensively irrigated regions such as South Fergana, alterations in soil microbial communities caused by irrigation regimes and anthropogenic pressure may influence nutrient cycling, food quality, and public health outcomes. Objective. This study aims to assess the microbiological activity of irrigated soils in the South Fergana region and to examine its associations with environmental health, food safety, and public health within the framework of the One Health concept. Methods. An integrated ecological–medical approach was applied to evaluate soil microbiological activity, focusing on microbial functional processes related to organic matter transformation, nitrogen cycling, and biological respiration. The analysis considered the potential health implications of disrupted microbial balance, including nitrate accumulation, mycotoxin formation, and the environmental spread of antibiotic-resistant microorganisms through agricultural products. Results. The findings indicate that optimal soil microbiological activity is closely associated with balanced irrigation practices and sustainable soil management. Disturbances in microbial processes were linked to increased ecological and health-related risks, particularly through compromised food safety and altered nutrient bioavailability. Enhanced microbial functionality contributed to improved soil quality and reduced potential public health hazards. Conclusion. Maintaining balanced microbiological activity in irrigated soils of South Fergana is essential not only for agricultural sustainability but also for safeguarding environmental and public health. The results underscore the importance of incorporating soil microbiological indicators into environmental health monitoring systems and support the implementation of the One Health approach in agroecosystem management.